A novel dual mechanism-of-action bispecific PD-1-IL-2v armed by a “βγ-only” interleukin-2 variant - Jiang, Yongji; Chen, Chuyuan; Liu, Yuan; Wang, Rong; Feng, Chuan; Cai, Lili; Chang, Shuang; Zhao, Lei (Frontiers in Immunology, 2024)
Introduction Interleukin-2 (IL-2) is one of the first cytokines to be discovered as an immune agonist for cancer immunotherapy. Biased IL-2 variants had been discovered to eliminate Treg activation or enhance the tumor specific T cell cytotoxicity. However, all the biased IL-2 variants pose the risk to overstimulate immune response at a low-dose range. Here, we introduce a novel dual-MOA bispecific PD-1-IL-2v molecule with great anti-tumor efficacy in a high dosed manner. Methods The novel IL-2 variant was designed by structural truncation and shuffling. The single armed bispecific PD-1-IL-2v molecule and IL-2v were studied by immune cell activations in vitro and in vivo and anti-tumor efficacy in mouse model. Results and discussion The IL-2 variant in this bispecific antibody only binds to IL-2Rβγ complex in a fast-on/off manner without α, β or γ single receptor binding. This IL-2v mildly activates T and NK cells without over stimulation, meanwhile it diminishes Treg activation compared to the wild type IL-2. This unique bispecific molecule with “βγ-only” IL-2v can not only “in-cis” stimulate and expand CD8 T and NK cells moderately without Treg activation, but also block the PD-1/L1 interaction at a similar dose range with monoclonal antibody.